Physical properties of sessile oak (quercus petraea l) used by the wood industry in Kosovo - Sejdiu, Rrahim; Hoxha, Florit; Jashari, Bujar; Idrizi, Lulzim (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The paper shows some physical properties of sessile oak obtained in Kosovo regions. In the study are shown: wood shrinkage, specific gravity, shrinkage coefficient for 1% change of moisture content, ratio of shrinkage in tangential and radial direction etc. The amount of volumetric shrinkage of sessile oak is 15.95%, heartwood part has an average shrinkage 15.41% in The shrinkage of sapwood part is 17.56%. Specific gravity at: wet condition: (1.013gr/cm3); 12% (0.853gr/cm3) and 0% (0.826gr/cm3) of moisture content. Specific gravity of heartwood at: wet condition (1.05gr/cm3); 12% (0.88gr/cm3); 0% (0.85gr/cm3). The specific gravity of sapwood at: wet condition (0.91gr/cm3); 12% (0.77gr/cm3); 0% (0.748gr/cm3). The ratio of average shrinkage between tangential and radial cutting direction is 1.71%. This ratio was significantly higher in sapwood than heartwood. Coefficient of shrinkage (changing 1% of moisture content) in the radial direction is 0.00196, and 0.00323 in tangential direction.